Structures, deformation history and dynamic background of the Qianyingzi Coal Mine in the Huaibei Coalfield, eastern China - Gu, Chengchuan; Zhai, Xiaorong; Wu, Jiwen; Li, Guangping; Wang, Xin; Tan, Pengfei; Hao, Hongjun (Frontiers in Earth Science, 2023)
The Qianyingzi Coal Mine is located in the west limb of the Sunan Anticline in the Suxian Mining District of the Huaibei Coalfield. The Carboniferous-Permian coal measure strata in the mine are generally a gentle syncline with a NNE axis and southward rising end, and are cut by a series of nearly N‒S-, NNE- to NE-striking faults. In this paper, based on the analysis of three-dimensional seismic data and regional tectonic correlation of mine, the structural development characteristics, evolution history and dynamic background of the Qianyingzi Coal Mine are discussed. The results show that: (1) The structures in the mine are mainly medium- and small-sized faults with a throw of less than 20 m, and the number of reverse faults is significantly greater than that of normal faults. The strike of both faults is mainly NE, followed by NNE and nearly N‒S. (2) The structural deformation of the coal measure strata can be divided into five stages: In the first stage, the Fengjia Syncline with NNE axis was developed; in the second stage, nearly N‒S-striking reverse faults were developed; in the third stage, NNE-striking reverse sinistral faults and NE-striking reverse faults were developed; the fourth and fifth stages are extensional structures, and nearly N‒S- and NW‒SE-striking normal faults were developed respectively. (3) The first and second shortening deformation structures in the mine are the results of foreland deformation and subsequent continent-continent collision during the convergence of the North China Craton and South China Plate in the Indosinian period. The third stage of compressional and transpressional structures is related to the rapid oblique subduction of the Izanagi Plate to the East Asian continental margin at the beginning of the Early Cretaceous in the western Pacific region. Finally, the fourth and fifth stages of extensional structures were developed under the backarc extensional background in eastern China during the Early Cretaceous.